A Systematic Study on the Effects of Process Parameters on Spinning of Thin-Walled Curved Surface Parts With 2195 Al-Li Alloy Tailor Welded Blanks Produced by FSW - Zhang, Hongrui; Zhan, Mei; Zheng, Zebang; Li, Rui; Lyu, Wei; Lei, Yudong (Frontiers in Materials, 2021)
The manufacturing process is inevitably accompanied with the production of scraps, which leads to resource waste and environmental pollution. Recycling and remanufacturing are the most commonly used approaches for metal scraps due to their well-established advantages from economic and environmental perspectives. In this study, spinning experiments with 2195 Al-Li alloy tailor welded blanks produced by friction stir welding from metal scraps were conducted under different process parameter designs. And then the effects of various process parameters on spinning of thin-walled curved surface parts were systematically studied. The results of the corresponding experimental groups show that the roller attack angle, the spinning clearance, and the installation method of tailor welded blanks have the most significant effect on the weld torsion angle. In addition, it was found that along the longitude direction of spun parts, the surface roughnesses of the weld of spun parts were greatly improved under the roller nose radius of 10 mm, the spinning clearance of 1.0 mm, the constant linear velocity, and the installation method of tailor welded blanks (the lower surface of tailor welded blanks is spun by rollers), while the process parameters have little significant effect on the surface roughness along the latitude direction of spun parts. Furthermore, it can be concluded that the forming profiles of spun parts fitted the mandrel well under the roller nose radius of 6 mm, double rollers, the roller attack angle of 30° and 45°, spinning clearance of 1.5 mm, and the installation method of tailor welded blanks (the upper surface of tailor welded blanks is spun by rollers). The research results will provide guidance for the precise spinning of thin-walled curved surface parts with tailor welded blanks. Thereby, it is also beneficial for green manufacturing involving recycling and remanufacturing of metal scraps.